2011
DOI: 10.1007/s11999-011-1877-z
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Infection Rate in Patients with Osteosarcomas Treated with Resection and Prosthetic Reconstruction

Abstract: Background The incidence of perioperative infection after segmental tumor endoprosthetic replacement in previous reports varies from a high of 7.4% to a low of 2.6%. Appropriate antibiotic use for this group is unknown and controversial, whereas the relationship of antibiotic use and perioperative infection is unclear. Questions/purposes We determined the incidence of perioperative infection in patients with osteosarcoma treated with segmental prosthetic replacement using a standard perioperative antibiotic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…Regarding the causes of delay in treatment duration, it is noteworthy to mention that up to a quarter of cases had infection‐related complications (mainly surgical wound infections) and febrile neutropenia, which resulted in delayed chemotherapy. The incidence of infectious episodes in our study is comparable with that observed in other studies from LMIC . However, both institutions are currently making some efforts to reduce infection‐related events by the implementation of an infection control committee and the early recognition of warning signs.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the causes of delay in treatment duration, it is noteworthy to mention that up to a quarter of cases had infection‐related complications (mainly surgical wound infections) and febrile neutropenia, which resulted in delayed chemotherapy. The incidence of infectious episodes in our study is comparable with that observed in other studies from LMIC . However, both institutions are currently making some efforts to reduce infection‐related events by the implementation of an infection control committee and the early recognition of warning signs.…”
Section: Discussionsupporting
confidence: 88%
“…Without the ability to control for these variables, it is difficult to draw precise conclusions about current infection rates. As a result, our quoted SSI rate of 10% reflects the rate over two decades and, therefore, may not precisely reflect the current rate of infection, which is Hardes et al [24] 2010 Antibiotics administered locally with a gentamicin-containing collagenous drug carrier; intravenous 3 rd -generation cephalosporin administered for 3-7 days postoperatively, followed by a 2 nd -generation cephalosporin administered orally until wound healed Li et al [40] 2011 Intravenous cephalosporin (1 g) administered intraoperatively; continued for 3 days postoperatively, then administered orally for an additional 5 days unknown. A multicenter prospective randomized study is underway to answer this question [15].…”
Section: Discussionmentioning
confidence: 91%
“…This rate is high compared with those of conventional knee and hip arthroplasties, which are reported to be between 0.5% and 2% [32,40]. The high infection rate among orthopaedic oncology patients is not surprising, however, and can be attributed to numerous factors.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations